Implementing a Spinosad-Based Local Bait Station to Control Bactrocera cucurbitae (Diptera: Tephritidae) in High Rainfall Areas of Reunion Island. Issue 1 (16th February 2015) - Delpoux, Camille; Deguine, Jean-Philippe
Abstract : Three species of fruit flies cause serious damage to cucurbit crops on Reunion Island: Bactrocera cucurbitae (Diptera: Tephritidae) (Coquillett 1899), Dacus ciliatus (Loew 1901), and Dacus demmerezi (Bezzi 1917). To control them, a program of agroecological management of cucurbit flies has been implemented based on the application of Synéis-appât, especially spot sprays on corn borders. However, the high rainfall on Reunion Island limits the long-term efficiency of the bait; in addition, this method cannot be used for large chayote trellises, because corn borders cannot be planted around them. The aim of this study was to design a bait station adapted to prevailing conditions on Reunion Island. An 'umbrella trap' tested in Taiwan was used as a reference to compare its efficacy with our local bait station. Experiments were conducted in field cages on B. cucurbitae to test different characteristics of bait stations and to construct one using local materials. Results were validated in the field. The attractiveness of the bait station was related mainly to the color of the external surface, yellow being the most attractive color. The efficacy of the bait station with respect to fly mortality was found to be linked to the accessibility of the bait, and direct application of Synéis-appât on the bait station was found to be the most efficient. In the field, B. cucurbitae were more attracted to the local bait station than to the umbrella trap, while the two other fly species displayed equal attraction to both trap types. Our local bait station is a useful alternative to spot sprays of Synéis-appât and is now included in a local pest management program and is well accepted by farmers.